2021
DOI: 10.1186/s13722-021-00256-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic equity in substance use treatment research: the way forward

Abstract: Background Opioid use and opioid-related overdose continue to rise among racial/ethnic minorities. Social determinants of health negatively impact these communities, possibly resulting in poorer treatment outcomes. Research is needed to investigate how to overcome the disproportionate and deleterious impact of social determinants of health on treatment entry, retention, drug use and related outcomes among racial/ethnic minorities. The current commentary provides recommendations that may help re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Also, this study utilized wave one of the PATH Study, collected nearly a decade ago and whose participants are now young adults. These findings provide a helpful juxtaposition with important findings using data from other sources collected during that time 43 . Still, the extent to which the findings apply to present day adolescents is unknown.…”
Section: Discussionmentioning
confidence: 55%
“…Also, this study utilized wave one of the PATH Study, collected nearly a decade ago and whose participants are now young adults. These findings provide a helpful juxtaposition with important findings using data from other sources collected during that time 43 . Still, the extent to which the findings apply to present day adolescents is unknown.…”
Section: Discussionmentioning
confidence: 55%
“…Data absenteeism is not unique to communication science but has become a point of continuous contention and advocacy, particularly among those who represent groups that have been neglected and even exploited by science and scientists. A resurgent advocacy movement both inside and outside the academy has begun to rigorously document the reasons behind data absenteeism in science, especially in basic and clinical sciences (Burlew, McCuistian, and Szapocznik 2021; Duma, Vera Aguilera, Paludo, et al 2018; Duma, Vera Aguilera, Wang, et al 2018), its consequences, and how to address it (Roundtable 2016). Advocates are also questioning the confidence in science that suffers from data absenteeism, also known as data chauvinism (Lee and Viswanath 2020), and raising questions about who owns the data.…”
Section: Conclusion: Toward An Inclusive Science Of Science Communica...mentioning
confidence: 99%
“…Many recent studies have highlighted the disparities depending on socioeconomic status, race/ethnicity, gender identity/biological sex, community, criminal history, and healthcare coverage. [5][6][7][8][9][10][11][12] For example, studies have shown that non-Hispanic Blacks and Hispanics are less likely to receive buprenorphine treatment compared to Whites, and women are less likely than men. 11,[13][14][15] Moreover, non-Hispanic Blacks and American Indians and Alaska Natives (AIAN) experienced the highest increases in the drug overdose mortality rates in 2019 and 2020, 16 while non-Hispanic Blacks experienced much higher increase of the mortality rates due to stimulants and opioids co-ingestion compared to non-Hispanic Whites.…”
Section: Introductionmentioning
confidence: 99%